1989
DOI: 10.1128/jb.171.7.3831-3839.1989
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the role of phospholipids in sexual reproduction by sterol-auxotrophic fungi

Abstract: Several genera of oomycete fungi which are incapable of de novo sterol synthesis do not require these compounds for vegetative growth. The requirement for an exogenous source of sterols for sexual reproduction by several members of the Pythiaceae has been questioned by reports of apparent induction and maturation of oospores on defined media supplemented with phospholipids in the absence of sterols. A more detailed examination of this phenomenon suggested that trace levels of sterols in the inoculum of some py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
(63 reference statements)
1
20
1
Order By: Relevance
“…When the putative sterols in 100 mg lecithin were isolated by column chromatography, and purified by digitonin precipitation, GC-MS analysis of the digitonide component failed to detect any sterols. The amount of putative sterols in the digitonide component of cephalin was also too small to be analysed by GC-MS. Kerwin & Duddles (1989) reported the detection of 631 and 587 ng cholesterol in two separate 1 g samples of 99 Yo synthetic dioleoyl phosphatidylcholine using GC-MS analysis. Based on their data, 100 pg phospholipids per basal medium disc used in this study should contain about 0-06 ng cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When the putative sterols in 100 mg lecithin were isolated by column chromatography, and purified by digitonin precipitation, GC-MS analysis of the digitonide component failed to detect any sterols. The amount of putative sterols in the digitonide component of cephalin was also too small to be analysed by GC-MS. Kerwin & Duddles (1989) reported the detection of 631 and 587 ng cholesterol in two separate 1 g samples of 99 Yo synthetic dioleoyl phosphatidylcholine using GC-MS analysis. Based on their data, 100 pg phospholipids per basal medium disc used in this study should contain about 0-06 ng cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial phase of this study, it was found that certain commercial samples of lecithins were stimulatory to oospore formation only after washing with deionized water. It is therefore suggested that the decrease of oosporogenesis reported in the literature (Kerwin & Duddles, 1989;Nes, 1988) could be due to the presence of inhibitory substances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…But a lack of sterol supply does not prevent the fungal growth of P. cactorum. Stimulation of reproduction-organ formation could be obtained by bringing phospholipids to P. cactorum [66,67] or to Pythium aphanidermatum [68], even with synthetic compounds, which avoids traces of sterol contaminations as was proposed to explain phospholipids activity [69]. It was also reported that unsaturated fatty acids as well as their triglycerides are good inducers of reproduction in P. cinnamomi [70] and in both P. cactorum and P. parasitica [71].…”
Section: Sterols In Oomycete Physiologymentioning
confidence: 99%